Why Democracies Produce Efficient Results - Wittman, Donald (Journal of Political Economy, 1989)
By applying the standard tools of microeconomic analysis, I argue that democratic markets work as well as economic markets. In particular, I show that previous work has greatly exaggerated the existence of principal-agent and informational problems in electoral markets and has drawn incorrect conclusions.